2015
DOI: 10.1017/s0007114515001178
|View full text |Cite
|
Sign up to set email alerts
|

Placental amino acid transport may be regulated by maternal vitamin D and vitamin D-binding protein: results from the Southampton Women's Survey

Abstract: Both maternal 25-hydroxyvitamin D (25(OH)D) concentrations during pregnancy and placental amino acid transporter gene expression have been associated with development of the offspring in terms of body composition and bone structure. Several amino acid transporter genes have vitamin D response elements in their promoters suggesting the possible linkage of these two mechanisms. We aimed to establish whether maternal 25(OH)D and vitamin D-binding protein (VDBP) levels relate to expression of placental amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…1,25-dihydroxy vitamin D 3 achieves this coordination by inducing innate antibacterial responses in human trophoblasts and inhibiting pro-inflammatory cytokines such as TNF-α and IL-6 (Liu et al, 2009; Noyola-Martinez et al, 2013). Although Cleal and colleagues recently identified an association between maternal serum 25-hydroxy vitamin D 3 concentrations and placental gene expression of amino acid transporters (Cleal et al, 2015), to the best of our knowledge vitamin D regulation of placental amino acid transporter activity has not previously been reported.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…1,25-dihydroxy vitamin D 3 achieves this coordination by inducing innate antibacterial responses in human trophoblasts and inhibiting pro-inflammatory cytokines such as TNF-α and IL-6 (Liu et al, 2009; Noyola-Martinez et al, 2013). Although Cleal and colleagues recently identified an association between maternal serum 25-hydroxy vitamin D 3 concentrations and placental gene expression of amino acid transporters (Cleal et al, 2015), to the best of our knowledge vitamin D regulation of placental amino acid transporter activity has not previously been reported.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, a study from the Southampton Women's survey demonstrated that maternal 25-hydroxyvitamin D and vitamin D binding protein levels were positively associated with placental expression of several amino acid transporter genes, suggesting placental amino acid transport may be regulated by maternal vitamin D and/or vitamin D-binding protein (Cleal et al, 2015). Previous studies in murine skeletal myotubes have shown that vitamin D enhances protein synthesis through mechanistic target of rapamycin (mTOR) signaling pathway (Salles et al, 2013) and we have reported that mTOR signalling is a positive regulator of amino acid transport in cultured primary human trophoblast (PHT) cells (Rosario et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that vitamin D deficiency correlates with various clinical conditions and parameters, including osteoporosis, cardiovascular diseases, autoimmune diseases, schizophrenia, surgical outcomes, and cancer risk [1213141516171819]. Nonetheless, the causality is still unproven.…”
Section: Introductionmentioning
confidence: 99%
“…, ); mechanistic investigations using placental samples have identified novel relationships between vitamin D and placental nutrient transport (Cleal et al . ).…”
Section: Dna Methylation and Bone Development: Potential Roles In Latmentioning
confidence: 97%
“…The results of this trial suggest that such a supplementary approach leads to improved offspring bone mineral content (of around 0.5 SD) compared with placebo, for neonates born in the winter months, when background 25(OH)D concentrations are lowest (although not in the population overall) . Subsequent work has identified interactions with both environmental and genetic factors in the achieved 25 (OH)D in response to treatment (Moon et al , 2017; mechanistic investigations using placental samples have identified novel relationships between vitamin D and placental nutrient transport (Cleal et al 2015). These candidate-focused studies contrast with findings from a recent investigation using the Illumina Human Methylation 450 BeadChip, an array covering methylation marks at over 450 000 CpG sites across the genome.…”
Section: Epigenetic Predictors Of Childhood Bone Healthmentioning
confidence: 98%